The effect of temperature on I-V characteristics and gamma rays on DNA molecule structure (Journal of Academic Research, 2024)
In the first part of this research, the I-V curves of DNA were studied at two temperatures (1°C ,25°C) and the identification and detection of DNA strands. The second part of the study using the effect of CO-60 radiation on DNA. UV radiation and radioactivity calculation in time periods (from 5 minutes to 3 hours) are also studied as well.The results of the research in the first part of the study showed that the DNA is a semiconductor material in the range of V (0-3.5) at a temperature of 1ºC for a period of 5 min, and at a temperature of 25ºC the DNA showed a semiconductor behavior in the range of mv (2-0) for a period of 5 min, and at exposed for an additional 5 min, the DNA molecule showed semiconductor behavior at values ​​​​of V (0-4.5) at a temperature of 25ºC. In addition, the resistance of the molecule is affected by the two temperatures, and the breakdown of the semiconductor material occurs at a current value of no more than 200 µA and voltage values ​​of 3.5V and 4V at 0.1ºC and 25ºC respectively.Our study provides practical, important data and results to know the movement of charges and the resistance of DNA at different temperatures, as well as radiation protection and avoid damage or genetic mutations.